Literature Review: The Role of Sustainability Reporting, Good Corporate Governance, and Profitability in Increasing Company Value - Maya Oktaviani; Titik Inayati (Al-Mal: Jurnal Akuntansi dan Keuangan Islam, 2025)
This study aims to examine the role of Sustainability Reporting, Good Corporate Governance (GCG), and Profitability in increasing company value. Through a Systematic Literature Review (SLR) of 11 articles published between 2019 and 2024, the results show that Sustainability Reporting and GCG have a positive effect on company value, with Profitability as a moderating variable that strengthens this relationship. The implementation of transparent ESG and good governance increases investor confidence, reduces information asymmetry, and encourages financial performance. The challenges faced include inconsistencies in reporting standards, weak supervision, and conflicts between short-term profit targets and long-term sustainability. This study produced a conceptual model that integrates SR, GCG, and profitability as strategies in creating sustainable company value.